2002
DOI: 10.1016/s0248-4900(02)01188-7
|View full text |Cite
|
Sign up to set email alerts
|

Endocytic prolactin routes to the secretory pathway in lactating mammary epithelial cells

Abstract: Plasma-borne prolactin is carried from blood to milk by transcytosis across the mammary epithelial cell through the endocytic and secretory pathways. To determine the precise route of prolactin endocytosis, intracellular transport of biotinylated prolactin was monitored, in parallel with endocytosis of fluorescein isothiocyanate-conjugated dextran and IgG, by using pulse-chase experiments in lactating mammary fragments and in enzymatically dissociated acini. Biotinylated prolactin was sorted to vesiculo-tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In parallel, we observed a significant reduction in the intracellular transport of prolactin in the transcytotic pathway of MECs. It was also shown that milk-protein synthesis drops and that the secretagogue effect of prolactin on their secretion disappears in lipid-restricted animals (Ollivier-Bousquet et al, 1993 and1997;Seddiki et al, 2002). These negative effects are reversed, at least in vitro, by the addition of 20:4 n-6 to mammary fragments (Ollivier-Bousquet et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, we observed a significant reduction in the intracellular transport of prolactin in the transcytotic pathway of MECs. It was also shown that milk-protein synthesis drops and that the secretagogue effect of prolactin on their secretion disappears in lipid-restricted animals (Ollivier-Bousquet et al, 1993 and1997;Seddiki et al, 2002). These negative effects are reversed, at least in vitro, by the addition of 20:4 n-6 to mammary fragments (Ollivier-Bousquet et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were washed and incubated with the appropriate fluorescence-conjugated secondary antibodies. Mammary tissues from lactating rats were fixed, frozen and cut as described (Seddiki et al, 2002). The sections were treated for immunofluorescence as described for acini.…”
Section: Immunofluorescencementioning
confidence: 99%
“…From blood, PRL is carried through the mammary epithelial cells (MECs) by transcytosis and is released into milk as intact and cleaved forms (Sinha, 1995;Ollivier-Bousquet, 1998). During this intracellular transport very little PRL is sorted to lysosomes (Seddiki and Ollivier-Bousquet, 1991;Seddiki et al, 2002). Consequently, the cleavage of PRL in these organelles might be relatively limited.…”
mentioning
confidence: 99%
“…The lactating MEC conveys newly synthesised milk proteins by a process involving considerable membrane flow, which is used now as a model of cisternal maturation trafficking [13,20,38]. Another type of endomembrane trafficking involves endocytosis of membrane-associated molecules, and a meeting of the endocytic and exocytic pathway has been described [50,61,62]. Such membrane traffic may be required at each stage of milk lipid droplet transport: formation in the ER, growth and transit, associated or not with secretory vesicles, and secretion after envelopment in the apical plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…(2) An endocytotic and transcytotic pathway involving internalisation of plasmaborne components into the cell and their transport into the milk [50]: during transport, a sorting of internalised molecules strictly controls the destination of the transcytosed products [41,61].…”
Section: Introductionmentioning
confidence: 99%